A Study on the Acceptance-Performance Correlation of Wechat English Learning in the Context of Digital Transformation: An Analysis Based on the Motivation-Enhanced TAM Framework - Xuelian, Wan; Zakaria, Megat Aman Zahiri bin Megat (Journal of Posthumanism, 2025)
This study constructs a motivation-enhanced Technology Acceptance Model (TAM) framework to explore the correlation mechanism between technology acceptance and learning performance in the WeChat English learning environment. Based on a 12-week follow-up study of 386 college students, Bayesian structural equation modeling and multi-level latent profile analysis were used to reveal the complex mechanism of motivational factors in the technology acceptance process. The research found that: (1) Four typical motivation combination patterns were identified through latent profile analysis, among which the balanced integration group (31.2%) showed the most adaptive learning behavior; (2) Intrinsic motivation showed a significant mediating effect ( Standardized indirect effect=.235, 95% CI [.156, .314]), and forms a positive synergy with perceived usefulness (β=.187, p<.001); (3) Learning engagement shows a sustained Three development trajectories: growth (38.4%), plateau-breakthrough (33.7%) and fluctuation-decay (27.9%); (4) Group-level factors (class atmosphere, teacher support, peer interaction) explained 12.3%- 18.7% effect variation. These findings not only extend the application of technology acceptance theory in the field of education, but also provide empirical evidence for optimizing language learning practices supported by social media.